2019
DOI: 10.1088/1751-8121/ab5426
|View full text |Cite
|
Sign up to set email alerts
|

The Kardar–Parisi–Zhang model of a random kinetic growth: effects of a randomly moving medium

Abstract: The effects of a randomly moving environment on a randomly growing interface are studied by the field theoretic renormalization group analysis. The kinetic growth of an interface (kinetic roughening) is described by the Kardar-Parisi-Zhang stochastic differential equation while the velocity field of the moving medium is modelled by the Navier-Stokes equation with an external random force. It is found that the large-scale, long-time (infrared) asymptotic behavior of the system is divided into four nonequilibriu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 111 publications
2
15
0
Order By: Relevance
“…We omit the one-loop calculations of the renormalization constants for brevity; see., e.g., [74] for similar calculations. In the one-loop approximation and minimal subtraction scheme (MS scheme) the renormalization constants Z ν and Z ν ⊥ read…”
mentioning
confidence: 79%
“…We omit the one-loop calculations of the renormalization constants for brevity; see., e.g., [74] for similar calculations. In the one-loop approximation and minimal subtraction scheme (MS scheme) the renormalization constants Z ν and Z ν ⊥ read…”
mentioning
confidence: 79%
“…Lastly, such coordinates do not preclude the existence of non-perturbative IR attractive fixed point that remains hidden in perturbative RG analysis. See a more detailed discussion of related issues in [68].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recent attempts [67][68][69] revealed that turbulent or random environment (modelled either by stochastic Navier-Stokes equation or by a "rapid-change" Kazantsev-Kraichnan velocity ensemble) dominates scaling and "washes away" the kinetic roughening.…”
Section: Introductionmentioning
confidence: 99%
“…The anomalous dimensions calculated from the Feynman graphs have the following one-loop expressions (we omit details of calculations 17 for brevity):…”
Section: Renormalization and Fixed Points Of The Model With Turbulent...mentioning
confidence: 99%